2017
DOI: 10.1002/clc.22683
|View full text |Cite
|
Sign up to set email alerts
|

Urinary [TIMP‐2] × [IGFBP7] for risk prediction of acute kidney injury in decompensated heart failure

Abstract: Background In acute decompensated heart failure (ADHF) the risk of acute kidney injury (AKI) is high. Early detection of patients at risk for AKI is important. We tested urinary [TIMP‐2] × [IGFBP7], a new US Food and Drug Administration–cleared test to assess AKI risk, in a cohort of hospitalized ADHF patients. Hypothesis In patients with ADHF, urinary [TIMP‐2] × [IGFBP7] is associated with moderate to severe AKI and related to increased mortality. Methods We enrolled 400 patients in the emergency department a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 29 publications
0
33
1
Order By: Relevance
“…Nevertheless, in patients with ADHF, Yang et al have shown that the incidence of AKI further increased to 47.6%[30]. This higher incidence of AKI in ADHF patients has been referred to as acute cardiac and renal dysfunction [31-34]. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in patients with ADHF, Yang et al have shown that the incidence of AKI further increased to 47.6%[30]. This higher incidence of AKI in ADHF patients has been referred to as acute cardiac and renal dysfunction [31-34]. …”
Section: Discussionmentioning
confidence: 99%
“…Further investigations will be needed to establish this association with HFpEF. Urinary IGFBP-7 levels are, together with tissue inhibitor of metalloproteinase 2 (TIMP-2), predictive for acute kidney injury in decompensated HF and post-coronary artery bypass surgery [92][93][94][95]. Thus, in addition to being a plasma biomarker, levels in other body fluids such as urine can provide diagnostic and/or prognostic information about patients.…”
Section: Metabolic Marker Igfbp-7mentioning
confidence: 99%
“…, which to some extent may be associated with the increased IGFBP-7, however when adjusted for these parameters the difference between the 2 HF groups remained statistically significant. Urinary IGFBP-7, along with TIMP-2, has in acute decompensated HF been suggested as a cell cycle arrest marker indicative of acute kidney injury(21). Cell cycle arrest is believed to be a protective mechanism initiated in the earliest stages of tubule cell stress/injury in response to insults, such as inflammation and oxidative stress, shutting down cell processes thereby protecting the cell from permanent damage or death.…”
mentioning
confidence: 99%